Mengapa Konsumen Bertahan? Minat Beli dan Loyalitas terhadap Produk Skincare Lokal - Ni Putu Ari Krismajayanti; Made Ratih Nurmalasari; Putu Putri Prawitasari; Ida Ayu Putu Megawati (Journal of Islamic Business Management Studies (JIBMS), 2025)
The local skincare industry in Indonesia has experienced rapid growth alongside increasing public awareness of skin health and personal appearance. Although the level of local skincare product usage is relatively high, this phenomenon is not always accompanied by the formation of strong consumer loyalty toward specific brands. This study aims to analyze consumer purchase intention and loyalty toward local skincare products, as well as to identify the factors influencing the development of such loyalty.This research adopts a qualitative approach using in-depth interviews with eight informants who are users of local skincare products in Denpasar City. The data were analyzed through processes of data reduction, data display, and conclusion drawing in order to obtain a comprehensive understanding of consumer behavior.The findings indicate that consumer beliefs regarding product safety, suitability for skin type, perceived benefits, affordable pricing, and ease of access are the primary factors driving purchase intention toward local skincare products. Beliefs formed through positive usage experiences play a crucial role in encouraging repeat purchases and fostering consumer loyalty. These findings emphasize that loyalty toward local skincare brands is not solely determined by product quality, but is also shaped by perceptions of safety, relevance to local needs, and consistent usage experiences. This study is expected to contribute to the development of consumer behavior research and to serve as a strategic reference for stakeholders in the local skincare industry.